Low cost industrial production of coagulation factor IX bioencapsulated in lettuce cells for oral tolerance induction in hemophilia B. (November 2015) - Su, Jin; Zhu, Liqing; Sherman, Alexandra; Wang, Xiaomei; Lin, Shina; Kamesh, Aditya; Norikane, Joey H.; Streatfield, Stephen J.; Herzog, Roland W.; Daniell, Henry
Abstract: Antibodies (inhibitors) developed by hemophilia B patients against coagulation factor IX (FIX) are challenging to eliminate because of anaphylaxis or nephrotic syndrome after continued infusion. To address this urgent unmet medical need, FIX fused with a transmucosal carrier (CTB) was produced in a commercial lettuce (Simpson Elite) cultivar using species specific chloroplast vectors regulated by endogenous psbA sequences. CTB-FIX (∼1 mg/g) in lyophilized cells was stable with proper folding, disulfide bonds and pentamer assembly when stored ∼2 years at ambient temperature. Feeding lettuce cells to hemophilia B mice delivered CTB-FIX efficiently to the gut immune system, induced LAP + regulatory T cells and suppressed inhibitor/IgE formation and anaphylaxis against FIX. Lyophilized cells enabled 10-fold dose escalation studies and successful induction of oral tolerance was observed in all tested doses. Induction of tolerance in such a broad dose range should enable oral delivery to patients of different age groups and diverse genetic background. Using Fraunhofer cGMP hydroponic system, ∼870 kg fresh or 43.5 kg dry weight can be harvested per 1000 ft 2 per annum yielding 24, 000–36, 000 doses for 20-kg pediatric patients, enabling first commercial development of an oral drug, addressing prohibitively expensive purification, cold storage/transportation and short shelf life of current protein drugs.